فراح غالي الصالحي تاثير مستوى الهيموغلوبين المسكر وفرط الاكسدة في مرشى السكري - فراح غالي (University of Thi-Qar Journal of Science, 2019)
This study was performed on (85) diabetic patients , classified as follows : 43patients of type I (25 male and 18 femels) and 42 patients of type II (24 malesand 18 femels .In addition , 55 healthy subjects were investigated as a controlgroup.Both types showed a highly significant increase (P=0.0001) in bloodglucose level ; 12.00 ± 3.96 mmole/l and 13.52 ±3.96 mmole/ l . for type I and IIrespectively compared to healthy subjects 4.63± 0.66 mmmole/l .This study also included the estimation of different biochemical parameters(Glycated hemoglobin HbA1c and malondialdehyde (MDA) in diabeticpatients, in which both types showed a highly significant increase (P=0.0001) inblood HbA1 level7.16 ± 0.62 μmole/l and 8.66 ± 0.50 μmole/l for type I and IIrespectively compared to healthy subjects 3.83 ± 0.40 μmole/l and in MDA level ; 12.22 ± 3.96 nmole/l and 13.52 ± 3.96 nmole/l for type I and IIrespectively compared to healthy subjects ; 14.63 ± 0.66 nmole/l .The results of this study revealed a positive correlation of blood glucose levelwith glycated hemoglobin HbA;c for diabetic patients –type I( CorrelationCoefficient =0.397) and type II (Correlation Coefficient =0.388 ) . Blood glucoselevel had a positive correlation also with malondialdehyde ( MDA) withcorrelation Coefficient =0.609 and 0.627 for type I and type II respectively .